CIRI KIMIA TANAH DAN BOBOT KERING BEBERAPA JENIS TANAMAN PUPUK HIJAU DENGAN PEMBERIAN KAPUR PADA TANAH MASAM - Siti Zahrah (Jurnal Ilmu Lingkungan, 2009)
This research was conducted in Green House and Soil Laboratory, Faculty of Agriculture,Andalas University. The research aim to study the effect of lime addition in acid soil to chemicalcharacteristic of soil and dry weigth of green manure crops. The experimental with CompletelyRandomized Design for Factorial 7x 2 were used. The first factor was green manure crops,consists of seven levels (Caliandra tetragona, Flemingia congesta, Gliricidia sepium, Leucaenaleucocephala, Leucaena glauca, Sesbania rostrata, Sesbania sesban) and second factor waslime addition, consists of two levels (without of lime and 1xAl-dd). The result of researchindicates that: (1) The liming can increase pH value from very acid (pH 4,45) to slighly acid(pH 5,60), decrease Al-dd content from 2,61 cmol/kg to 1,12 cmol/kg (57,09%), decrease Alsaturation from 74,78% to 49,12% (34,31%); (2) The highest dry weight at cutting I wasSesbania sesban with liming 1xAl-dd (26,39 g/pot); cutting II was Gliricidia sepium with liming(24,40 g/pot); cutting III was Gliricidia sepium with liming (17,90 g/pot), and cutting IV wasFlemingia congesta with liming ( 29,66 g/pot).